KAJIAN KESIAPSIAGAAN TERHADAP BENCANA TSUNAMI DI KECAMATAN PURING KABUPATEN KEBUMEN TAHUN 2016 - Kukuh Setio Utomo; Chatarina Muryani; Setya Nugraha (GeoEco, 2018)
This study aims to determine : (1) Preparedness of individuals to tsunamis in Puring SubDistrict Kebumen Regency (2) Preparedness of school comunity to tsunamis in Puring Sub-District Kebumen Regency (3) Preparedness of government to tsunamis in Puring Sub-District Kebumen Regency (4) Efforts made by individuals, school community, and goverment to improve tsunami preparedness in Puring Sub-District Kebumen Regency. This study is a qualitative study using a spatial approach. A sampling technique that Area Probability sample. Data were analyzed using index formula guides sourced from LIPI (2006) and elaborated descriptively. The results showed that (1) Preparedness of individuals included in the category of ready with an average index value of 67.06. (2) School community preparedness included in the category of ready with an average index value of 68.25. (3) Government preparedness included in the category of ready with an average index value of 68. (4) The efforts made by individuals to improve preparedness by following the socialization and simulation. Schools apply knowledge of disaster in the learning material, whereas the government conduct socialization to the public and coordination with the relevant parties. Keywords: Disaster, Tsunami, Disaster Preparedness, Individual, Household, Community Schools, Government